MEASUREMENTS OF SINGLE-MODE FIBER OPTICS ATTENUATION/LOSS USING BIDIRECTIONAL TEST TECHNIQUE - Ilouno, J.; Awoji, M.; Akeredolu, B. J.; Kwaha, B. J.; Chagok, N. M. D. (FUDMA Journal of Sciences, 2023)
One of the effects of attenuation in fiber link is the weakening of the strength of signal as it travels down the fiber. This effect, if not checked or controlled, leads to poor quality network or communication failure. An Optical Time Domain Reflectometer (OTDR) was used to measure the actual attenuations in single-mode fiber using bidirectional techniques. This method handled the limitations posed by the mono-directional technique. The OTDR was able to establish the attenuation in every portion of the fiber under test. Averaging the two mono-directional results (bidirectional analysis) gave a better attenuation limit of 0.191dB/km for 1550 nm signal over the span length of 16.60 km which is within the acceptable standard range of 0.20 dB/km to 0.30 B/km. Hence, quality signal transmissions can be achieved along these routes (fiber core 05 to core 32).
Keywords: Attenuation, OTDR, Bidirectional, Mono-directional